Test anxiety inventory-State: Preliminary analysis of validity and reliability in psychology college students - Dominguez-Lara, Sergio (2016)
The objective of the present study was to examine the internal structure of the Test anxiety inventory-State (TAI-State) in Spanish version. A sample of 125 college students from Lima (84.8% female) between 18 and 31 years old (M = 22.51) was evaluated. The internal structure of the STAI was analyzed by a confirmatory factor analysis, evaluating three models: oblique, bifactor and unidimensional. The results indicate that a single dimension constitutes the STAI and there are coefficients of reliability with high magnitudes. In conclusion, the version studied shows favorable psychometric properties that support its use in Lima.